Elucidating the underlying causes of oral cancer through spatial clustering in high-risk areas of Taiwan with a distinct gender ratio of incidence - Chiang, Chi-Ting; Hwang, Yaw-Huei; Su, Che-Chun; Tsai, Kuo-Yang; Lian, Ie-Bin; Yuan, Tzu-Hsuen; Chang, Tsun-Kuo (Geospatial health, 2010)
This study aimed to elucidate whether or not high-risk clusters of oral cancer (OC) incidence spatially correlate with the prevalence rates of betel quid chewing (BQC) and cigarette smoking (CS) in Taiwan. The spatial autocorrelation and potential clusters of OC incidence among the 307 townships and heavy metal content of soil throughout Taiwan were identified using the Anselin's local Moran test. Additionally, the spatial correlations among the incidence of OC, the prevalence of BQC and CS and heavy metal content of soil were determined based on a comparison of spatial clusters. High-risk OC (Moran's I = 0.638, P <0.001) clusters were located in central and eastern Taiwan, while "hot spots" of BQC and CS prevalence were located mainly in eastern Taiwan. The distributions of BQC and CS lifestyle factors (P <0.001) were spatially autocorrelated. The "hot spots" of OC largely coincided with the "hot spots" of BQC, except for the Changhua and Yunlin counties, which are located in central Taiwan. However, high soil contents of nickel and chromium (P <0.001) in central Taiwan also coincided with the high-risk areas of OC incidence. In particular, Changhua county has incurred several decades of serious heavy-metal pollution, with inhabitants living in polluted areas having high-risk exposure to these metals. Results of this study suggest that, in addition to BQC and CS, anthropogenic pollution may profoundly impact the complexity of OC aetiology in central Taiwan.